The Answer to the Groundlessness of a New Way of Development of Giftedness - D.B. Bogoyavlenskaya; G.P. Pirlik (Moscow State University of Psychology and Education, 2023)
The article substantiates the objection to V.S. Yurkevich to present the posi[1]tion towards understanding giftedness and developing creativity. The main objection is related to the thesis that the search activity "lies on the surface", but has not been investigated by anyone. In addition, the definition of giftedness only in terms of the height of abilities, with the absence of manifestations of creativity emphasized by the author, separates giftedness from creativity. At the same time, the spread of understanding of giftedness as high abilities implied the possibility of manifestations of creativity. The studies of V.S. Rotenberg, V.V. Arshavsky the biological concept of search activity. The correlation of primitive forms of search activity, which ensure survival through adaptation, and higher forms of human behavior – search and research activities and creativity (phenomena of pre-adaptation), which are based on cognitive motivation, are substantiated. An indication of the presence of search activity in its various forms in the scientific concepts and practice of education is given.